Penerapan dan Evaluasi PSAP Nomor 13 dalam Penyajian Laporan Keuangan (Studi pada Universitas Pendidikan Ganesha) - Intan Kesuma Dewi, A.A. Sagung; Muliartha, Ketut (E-Jurnal Akuntansi; Vol 31 No 2 (2021), 2021)
This research was conducted with the aim of knowing and evaluating the application of PSAP Number 13 in presenting the financial statements of Universitas Pendidikan Ganesha. This research uses qualitative methods with the approach used is a case study approach. Data obtained through documentation, observation, and in-depth interviews. The results in this study indicate that Universitas Pendidikan Ganesha has referred to PSAP Number 13. There are several obstacles found in the preparation of the financial statements which are, 1) the understanding of human resources in the use of the accrual basis is not yet comprehensive 2)  the  used  of  decentralized  system  in  financial management creates an biased information. Keywords:  PSAP Number 13; Financial Reports;  Public Service  Agency.